2013
DOI: 10.1371/journal.pone.0071060
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Simulation and Metabolome Analysis of Long-Term Erythrocyte Storage in Adenine–Guanosine Solution

Abstract: Although intraerythrocytic ATP and 2,3-bisphophoglycerate (2,3-BPG) are known as direct indicators of the viability of preserved red blood cells and the efficiency of post-transfusion oxygen delivery, no current blood storage method in practical use has succeeded in maintaining both these metabolites at high levels for long periods. In this study, we constructed a mathematical kinetic model of comprehensive metabolism in red blood cells stored in a recently developed blood storage solution containing adenine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 29 publications
2
47
0
Order By: Relevance
“…Previous metabolomics studies have focused on the impact of metabolic lesions on RBC viability during storage in the presence of different ASs, including SAGM, MAP, PAGGGM, and AS‐5 . Accordingly, we focus here on RBC storage in AS‐3, an AS that is characterized by half the level of saline in comparison to SAGM, AS‐1, and AS‐5 (70 mmol/L vs. 150, 154, and 150 mmol/L, respectively), high phosphate loading (23 mmol/L NaH 2 PO 4 , absent in other ASs, and only 5 mmol/L in MAP), almost a double dose of adenine in comparison to SAGM (2 mmol/L vs. 1.2 mmol/L) and half the dose of dextrose in comparison to AS‐1 (55 mmol/L vs. 111 mmol/L) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous metabolomics studies have focused on the impact of metabolic lesions on RBC viability during storage in the presence of different ASs, including SAGM, MAP, PAGGGM, and AS‐5 . Accordingly, we focus here on RBC storage in AS‐3, an AS that is characterized by half the level of saline in comparison to SAGM, AS‐1, and AS‐5 (70 mmol/L vs. 150, 154, and 150 mmol/L, respectively), high phosphate loading (23 mmol/L NaH 2 PO 4 , absent in other ASs, and only 5 mmol/L in MAP), almost a double dose of adenine in comparison to SAGM (2 mmol/L vs. 1.2 mmol/L) and half the dose of dextrose in comparison to AS‐1 (55 mmol/L vs. 111 mmol/L) .…”
Section: Discussionmentioning
confidence: 99%
“…During storage, RBCs are characterized by the progressive accumulation of biochemical products commonly known as the “storage lesion.” The storage lesion results in the impairment of cation homeostasis, the accumulation of reactive oxygen species, the alteration of proteomic profiles, and the progressive vesiculation of membrane portions that accompanies the loss of the discocytic morphology in exchange for a spheroechinocytic RBC morphology . Metabolomics studies have been completed on RBC units stored in a number of additive solutions (ASs), including SAGM, AS‐1, MAP, PAGGGM, and AS‐5 . These studies paved the way for preliminary investigations aimed at determining the influence of alternative storage solutions (e.g., supplementation of antioxidants, vitamin C, N ‐acetylcysteine, or serotonin) or strategies (such as anaerobic storage) on stored RBC metabolic profiles.…”
mentioning
confidence: 99%
“…[2][3][4][5] In recent years, the storage lesion has been extensively studied through integrated omics and systems biology approaches. 4,[6][7][8][9][10][11][12][13][14][15][16][17] We recently reported how metabolomics was able to reveal a clear metabolic signature descriptive of the RBC storage lesion. 10 Then, we demonstrated that RBCs stored in the blood bank do not simply undergo a monotonic decay, but experience a more complex change in metabolism that involves the development of 3 discrete metabolic phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics investigation of RBC lesion during storage in the blood bank have recently highlighted common and unique patterns depending on the AS in which RBCs are stored, AS‐1, AS‐3, or AS5 in the United States or SAGM, MAP, and PAGGGM in Europe and other countries. In this respect, encouraging results have been observed when storing RBCs in presence of alkaline solutions such as AS‐7, previously known as EAS‐81 …”
mentioning
confidence: 99%